RLS Beamforming Algorithm Based on Wavelet Transform - Jihong Zhao; Pei Lei; Weihua Wang; Hua Qu; Dan He (Dianxin kexue)
On the basis of analyzing the recursive least square algorithm（RLS）, in order to improve the performance of RLS algorithm, the idea of denoising by wavelet transform was introduced and the RLS beamforming algorithm which is based on wavelet transform was put forward. This algorithm uses soft thresholding wavelet transform for signal denoising, solves the problem that the traditional Adaptive beamforming algorithm is sensitive to noise and the steady-state error is big under the environment of the low signal to noise ratio（SNR）and small forgetting factor. Finally, the simulation results show that compared with the traditional RLS algorithm, this algorithm has smaller steady-state error and fast tracking speed and convergence speed, and good results of beamforming.